Compound odontoma: A case report on 42 denticles hodgepodge in maxilla - Shrestha, Sneha; Rai, Amita; Koirala, Bandana; Dali, Mamta; Shrestha, Ashish (Birat Journal of Health Sciences, 2022)
Compound odontomas are the commonest benign odontogenic tumours of jaws affecting mostly children and adolescents. These developmental malformations display many tooth-like structures or denticles that consist of well-defined dental tissues with diverse morphologies. Majority of these lesions occur as intraosseous masses in the maxillary anterior region and are incidental radiographic findings. These are primarily associated with retention of primary teeth and delayed eruption of permanent teeth. The preferred treatment for these lesions is conservative surgical excision followed by a histopathological diagnosis. This case report presents a rare case of compound odontoma displaying numerous denticles (42 in number) in the maxillary anterior region of a 12-year-old male child and its surgical management.